Technology transfer experiences in the Mediterranean - Gauci-Borda I.; Koc Y.; Fysekidis A. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
One of the important outputs of the MIRA project has been the creation of the Euro-Mediterranean Innovation Space (EMIS). This concept has allowed to initiate a number of activities among interested stakeholders in the Mediterranean who meet and discuss the framework conditions necessary to create such a Space. A case in point is represented by the TT activities organised to this effect. MIRA organised an exploratory forum in this regard in Brussels, Belgium (February 2010); other forums were organised in Casablanca, Morocco (December 2011), in Tunis, Tunisia (June 2012) and in Larnaca, Cyprus (October 2012). The Brussels event identified four key issues namely: Identification and mapping of the key barriers and the success factors; Knowledge Transfer policies and strategies; Innovation strategies and entrepreneurship in a Euro-Mediterranean context; Building knowledge and technology transfer capacities. A number of recommendations were drawn up based on the personal experiences of the participants coming from both sides of the Mediterranean. One important issue which emerged is the need to have clear achievable aims at two levels, both national and regional; more importantly, these aims must be designed in a way that they are complementary to each other.